Pengaruh Komposisi Media Tanam dan Konsentrasi Limbah Tahu Terhadap Pertumbuhan dan Hasil Tanaman Okra (Abelmoschus esculentus L.) - Purwita Sari Nugraini; Gregorius Hadi Sumartono; Etik Wukir Tini (Fapetrik-UMPAR, 2020)
Okra has many benefits as a functional food that can reduce blood sugar. The production of okra in Indonesian has not achieved maximum results, so needed a research to increase okra production. This study aims to find out the right composition of planting media, optimum concentration of organic tofu liquid fertilizer, determine the combination of planting media composition and concentration of organic tofu liquid waste fertilizer which can increase the growth and yield of okra plants. This research was conducted in Januari 2020 until April 2020 at the Greenhouse of the Organic Vegetable Pager Gunung, Melung village. Baturaden in Banyumas Regency. The experimental design used a Complete Randomized Block Design (RCBD) with 2 factors. The first factor is the composition of the planting medium, namely soil, soil + husk charcoal, soil + bokashi + husk charcoal. The second factor is the concentration of organic tofu liquid waste fertilizer, namely control, 20%, 40%, and 60%. The observed variables were plant height, stem diametre, number of leaves, leaf area, root length, flowering time, number of fruits, fruit weigh, plant fresh weight, plant dry weight. The data obtained were analyzed by DSTAAT. Further tests using DMRT at a level of 5%. The results showed that the best application media is soil + bokashi + husk charcoal which produces a plant height of 63.33 cm, stem diametre 10.11 cm, number of leaves 8.61 strands, leaf areas 1066.76 cm3, flowering time 46.97 day, number of fruits 3.38, fruit weight 41.48 g, fresh weight of plants at 102.01 g and dry weight of plants at 12.98 g. Provision of soil + husk charcoal produces a root length at 37.13 cm. Application of tofu waste fertilizer with a concentration was not able to increase the growth and yield of okra.